THE EFFECT OF COVID-19 ON THE ORGANIZATIONAL PERFORMANCE OF EMPLOYEES IN THAILAND - Sorasak Tangthong (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Pandemics such as Covid-19 are a severe pandemic with significant consequences for both business and employees' performances globally which Thailand is no exception. The Covid19 related impact on the productive economic mechanisms such as the employees through domestic lockdowns has disrupted the world of the working class in the first and second quarter of 2020 in Thailand. There are threatening economic signals that this might deepen in the remaining months of this year. The entire sectors (medium or high) at risk experienced low economic output due to Covid-19 that diminish working hours and wages or worse still complete job loss especially in the second quarter of the pandemic in Thailand. The job disruption has affected 6.6 to 7.5 million workers in the first quarter of 2020. The paper cited the research gap of crisis attributed to the financial crisis and natural disasters which Covid19 is the first to cripple global economies more any natural or artificial crises. The focus is on how to counter-intuitive implications for workers (human resources) functioning in Covid-19 period that suggest organizational fair forums to manage and supervise corporate responses to employees' conditions for encouraging business recovery in Thailand. The paper cites the role of organizational management in mitigating the effects of Covid-19 through labour retention, employee performance, and other variables such as pay cuts, businesses lockdown/shut down and operational shifts